2013
DOI: 10.1080/07448481.2012.747526
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intakes and Eating Habits of College Athletes: Are Female College Athletes Following the Current Sports Nutrition Standards?

Abstract: Effective nutrition interventions are needed to improve dietary intakes and eating habits of female college athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 28 publications
5
66
0
8
Order By: Relevance
“…A restrição calórica observada pode ter sido em função da grande prevalência de atletas de modalidades de resistência aeróbia e lutas que são beneficiados pelo programa (70% dos homens e 84% das mulheres, p>0,05). Atletas dessas modalidades tendem a adotar estratégias de restrição alimentar a fim de manter o peso ideal, adquirir um baixo percentual de gordura e maior agilidade 5,6 .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…A restrição calórica observada pode ter sido em função da grande prevalência de atletas de modalidades de resistência aeróbia e lutas que são beneficiados pelo programa (70% dos homens e 84% das mulheres, p>0,05). Atletas dessas modalidades tendem a adotar estratégias de restrição alimentar a fim de manter o peso ideal, adquirir um baixo percentual de gordura e maior agilidade 5,6 .…”
Section: Discussionunclassified
“…Entretanto, apesar do elevado número de trabalhos envolvendo mulheres atletas, essas conclusões são advindas daqueles que avaliaram o gênero feminino de forma isolada 5,6 . Além…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Erdman [12] reported that 98% of elite Canadian male athletes consumed breakfast, while Shriver et al [42] at the same year found that only 23% of elite college female athletes consumed breakfast. The majority of the athletes in the second study reported their diets to be poor, most of the calories were consuming at dinner and they found it difficult to maintain their weight.…”
Section: Timing Of Food Consumption During Training and Throughout Thmentioning
confidence: 99%